An Action Research on Open Knowledge and Technology Transfer - Ramos, Isabel; Cardoso, Margarida; João Carvalho; Graça, José (Information Systems – Creativity and Innovation in Small and Medium-Sized Enterprises, 2009)
R&D has always been considered a strategic asset of companies. Traditionally, companies that have their own R&D function are better prepared to compete in the globalized economy because they are able to produce the knowledge and technology required to advance products and services. SMEs also need to become highly innovative and competitive in order to be successful. Nevertheless, their ability to have an internal R&D function that effectively meets their innovation needs is usually very weak. Open innovation provides access to a vast amount of new ideas and technologies at lower costs than closed innovation. This paper presents an action research study being carried out at University of Minho to develop a business model and technology platform for an innovation brokering service connecting ideas and technologies being developed at Universities with the specific innovation needs of SMEs. The expected contributions of the study include the empirical investigation of the effectiveness and risks of crowdsourcing innovation when applied in the socio-economic context of a European developing country where SMEs represent 99,6% of the businesses.

Challenges of Consumer Information Systems Development: The Case of Interactive Television Services - Tuunanen, Tuure; Michael D. Myers; Cassab, Harold (Advances in Information Systems Research, Education and Practice, 2008)